Therapeutic Management of Canine Dirofilariasis in Nagaland, India - Kuotsu, Keneisezo; Ozukum, Sashitola; Kuotsu, Neithono; Devi, N Bhumapati; Laltlankimi,; Chutia, Tukheswar; Biswas, Newton; Das, Gunjan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Dirofilariasis is one of the most clinically important diseases  in dogs. It is also called as heart-worm disease, which is a  non-contagious parasitic disease caused by filarial or small  thread-like worms, Dirofilaria immitis, and D. repens of the  family Onchocercidae (Nelson et al., 2014; Adebayo et al., 2022).  It is an arthropod-borne disease. The mosquitoes belonging  to the genera Culex, Aedes, Anopheles, and Mansonia are  principally responsible for the transmission of this disease  (Borthakur et al., 2016). Transmission of the parasite occurs  when a potential vector bites dogs during a blood meal.  It takes about 6-7 months for the third-stage larvae (L3) to  become adult parasites after entering the blood vessels of  the hosts (Koutsu et al., 2022).  After maturation, the adult  worms reproduce and produce microfilariae (pre-L1), which  are released in the host blood vessels and taken up by a  feeding mosquito (Thilakarathne et al., 2023), and completed  the lifecycle of the parasite.
Keywords: Therapeutic; Canine; Dirofilariasis